Dose Optimization of Calcusol™ and Calcium Oxalate Monohydrate (COM) on Primary Renal Epithelial Cells Cultures of Mice (Mus musculus) - Ahmad Soni; Muhammad Sasmito Djati; Sri Widyarti (Journal of Tropical Life Science, 2014)
Kidney stones are one of the urologic diseases that have plagued mankind for centuries. The main constituents of stones in the kidney are calcium oxalate monohydrate (COM) crystals. Nowadays, there are varieties of drugs and treatments that can be made to minimize the grievances due to kidney stone disease. The treatment can be done either by using chemicals or traditional medicine. Calcusol™ is one of the popular herbal products that have been used by Indonesian people in curing the kidney stone disease. The main constituent that was contained in Calcusol™ is an extract of the tempuyung leaves (Sonchus arvensis L.), which is expected could cure the kidney stone disease. This study used primary cultured renal epithelial cells of mice to determine the optimal dose of Calcusol and the optimal dose of COM. The primary Kidney epithelial cell were treated with Calcusol™ and COM at various doses. The analysis of the cell death either by necrosis or apoptosis pathways was analyzed by flow cytometric analysis. The results that were obtained is the percentage of cell death that is then analyzed by using a complete randomized design (CRD) One Way Anova. Based on the results that were obtained, it is known that the optimal dose of Calcusol™ in vitro were ranging from 75 ppm to 100 ppm, whereas the optimal dose of COM suggested for 500 ppm.